Health Literacy Mediates the Relationship Between Educational Attainment and Health Behavior: A Danish Population-Based Study. (1st August 2016) - Friis, Karina; Lasgaard, Mathias; Rowlands, Gillian; Osborne, Richard H.; Maindal, Helle T.
Abstract : Individuals with a lower education level frequently have unhealthier behaviors than individuals with a higher education level, but the pathway is not fully understood. The aim of this study was to investigate whether health literacy mediates the association between educational attainment and health behavior (smoking, physical inactivity, poor diet) and obesity. The study included respondents ages 25 years or older drawn from a large population-based survey conducted in 2013 ( N = 29, 473). Two scales from the Health Literacy Questionnaire were used: (a) Understanding health information well enough to know what to do and (b) Ability to actively engage with health care providers. Multiple mediation analyses were conducted using the Karlson-Holm-Breen method. The study showed that health literacy in general and the ability to understand health information in particular mediated the relationship between educational attainment and health behavior, especially in relation to being physically inactive (accounting for 20% of the variance), having a poor diet (accounting for 13% of the variance), and being obese (accounting for 16% of the variance). These findings suggest that strategies for improving health behavior and reducing health inequalities may benefit from adopting a stronger focus on health literacy within prevention, patient education, and other public health interventions.